Use of closed systems in the Hospital Pharmacy - María Forte Pérez-Minayo; Eva Castillo Bazán; Marta Hernández Segurado; María Ángeles Arias Moya; Paloma Pelegrín Torres; Francisco Javier Bécares Martínez (Elsevier, 2016)
Objective: In the setting of the increasing use of closed systems for reconstitution and preparation of these drugs, we intend to analyze the correct use of these systems in the Hospital Pharmacy, with the objective to minimize the risks of exposure not only for those professionals directly involved, but also for all the staff in the unit, taking also into account efficiency criteria. Method: Since some systems protect against aerosol formation but not from vapours, we decided to review which cytostatics should be prepared using an awl with an air inlet valve, in order to implement a new working procedure. We reviewed the formulations available in our hospital, with the following criteria: method of administration, excipients, and potential hazard for the staff handling them. We measured the diameters of the vials. We selected drugs with Level 1 Risk and also those including alcohol-based excipients, which could generate vapours. Outcomes: Out of the 66 reviewed formulations, we concluded that 11 drugs should be reconstituted with this type of awl: busulfan, cabazitaxel, carmustine, cyclophosphamide, eribulin, etoposide, fotemustine, melphalan, paclitaxel, temsirolimus and thiotepa; these represented an 18% of the total volume of formulations. Conclusions: The selection of healthcare products must be done at the Hospital Pharmacy, because the use of a system with an air valve inlet only for those drugs selected led to an outcome of savings and a more efficient use of materials. In our experience, we confirmed that the use of the needle could only be avoided when the awl could adapt to the different formulations of cytostatics, and this is only possible when different types of awls are available. Besides, connections were only really closed when a single awl was used for each vial. The change in working methodology when handling these drugs, as a result of this study, will allow us to start different studies about environmental contamination as a future line of work.